Structured Equation Modelling on Consumer Purchase Behaviour of Passenger Cars. Issue 2 (June 2018) - Menon, Balakrishnan
With increased globalization, many prominent leaders in car manufacturing industry across the world have built their manufacturing units in India, through the application of direct investment collaboration route with Indian companies, by using the liberalized foreign direct investment (FDI) policy of the Indian Government. With multiple selective choices to consumers, the car segments have undergone a metamorphosis in India. With many makes, brands and models, customers have many choices currently. The predominant purpose of this article is to conceptualize and design a purchase decision model, which would strongly provide an orientation of determinants, which influenced the consumer buyer behaviour of passenger car owners. The study results conclusively validated that eight major variables strongly influenced the consumer purchase behaviour of car owners. The major findings of the study would facilitate practical application, specifically, in the highly segmented passenger car markets in India.